Evaluating the Effectiveness of Zoning-Based Student Admission Policy: A Qualitative Study of Junior High Schools - Firdaus, Fadli (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
As a national policy, we introduced the zoning system to ensure equitable access to education and reduce the concentration of students in